2020
DOI: 10.1080/14681366.2020.1794947
|View full text |Cite
|
Sign up to set email alerts
|

Museum education, cultural sustainability, and English language teaching in Spain

Abstract: The collaborative action research project presented analysed the potential of museum education to radically transform the way in which English was taught and learnt in three diverse elementary, middle, and high-school contexts in the province of València (Spain). Insights from museum education and New Literacy Studies were used to expand upon the pedagogical affordances of the material and multimodal dimensions of English language teaching, in order to generate more opportunities for student motivation and eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Interest in learning is the desire to make changes and improvements in a person, from not knowing to know, from being unable to be able, according to what they want (Rauf, 2013;Christensen-Scheel, 2018;Villacañas de Castro, et al, 2020). In simple terms, interest means a tendency and high excitement or a great desire for something.…”
Section: Students' Art Learning Interestmentioning
confidence: 99%
“…Interest in learning is the desire to make changes and improvements in a person, from not knowing to know, from being unable to be able, according to what they want (Rauf, 2013;Christensen-Scheel, 2018;Villacañas de Castro, et al, 2020). In simple terms, interest means a tendency and high excitement or a great desire for something.…”
Section: Students' Art Learning Interestmentioning
confidence: 99%
“…In ESL instruction, social spaces such as museums can be utilised to achieve the goals of inculcating learner engagements with various modes and forms of meaning making. Museums enrich learning identities and experiences, allowing learners to socialize as they share their work in the target language (Villacañas de Castro et al, 2022) and, as a hybrid space, it reinforces disciplinary literacy education (Deroo & Galante, 2022). Previous studies have also shown that museum activities boosted language learners' confidence as they engaged with peers outside the formal classroom (Fazzi & Lasagabaster, 2021).…”
Section: Introductionmentioning
confidence: 99%